2009
DOI: 10.1158/0008-5472.can-08-3403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Deregulated Signaling Converging onto mTOR with Prognosis and Classification of Lung Adenocarcinoma Shown by Two Independent In silico Analyses

Abstract: There is marked disparity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…We tested this hypothesis and confirmed that the mutant NRF2 signature is indeed a prognostic factor in SCC of the head and neck region and probably that of the lung. Interestingly, an independent study focusing on the prognostic molecular pathway in lung adenocarcinoma has identified the Peng_Rap_DN pathway, a top-ranking gene set enriched in mutant NRF2 clones, as a signature that is significantly associated with poor prognosis (46). This also supports our contention that the mutant NRF2 signature is a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…We tested this hypothesis and confirmed that the mutant NRF2 signature is indeed a prognostic factor in SCC of the head and neck region and probably that of the lung. Interestingly, an independent study focusing on the prognostic molecular pathway in lung adenocarcinoma has identified the Peng_Rap_DN pathway, a top-ranking gene set enriched in mutant NRF2 clones, as a signature that is significantly associated with poor prognosis (46). This also supports our contention that the mutant NRF2 signature is a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…The validation analyses also showed the heterogeneity of tumors across data sets and possibly across regions of the World. For example, in our set of North American AD, mTOR was not found to be an important predictor of survival (due to a high correlation with pathways that were not selected out of the model), but in both validation sets higher expression of the mTOR pathway was associated with poorer outcome which is consistent with previous reports [15]. Also, increased cell proliferation and a larger solid component was highly significant in both the North American and the Japanese lung cohorts, although not in the mostly stage 1 French cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Rapamycin in complex with FKBP12 interacts with mTOR and inhibits its activity in the mTORC1 complex (26). mTOR activity is increased in many tumors, including lung cancer (27); inhibition of mTOR function through rapamycin analogues is considered as promising therapeutic strategy. Earlier reports have suggested that activation of mTOR is a Smad-independent TGF-β pathway that regulates protein synthesis, complementing the Smad-mediated transcriptional regulation (28).…”
Section: Discussionmentioning
confidence: 99%